2022
DOI: 10.1302/0301-620x.104b7.bjj-2021-1628.r1
|View full text |Cite
|
Sign up to set email alerts
|

Modular dual-mobility articulations in patients with adverse spinopelvic mobility

Abstract: Aims Adverse spinal motion or balance (spine mobility) and adverse pelvic mobility, in combination, are often referred to as adverse spinopelvic mobility (SPM). A stiff lumbar spine, large posterior standing pelvic tilt, and severe sagittal spinal deformity have been identified as risk factors for increased hip instability. Adverse SPM can create functional malposition of the acetabular components and hence is an instability risk. Adverse pelvic mobility is often, but not always, associated with abnormal spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Of the 63 articles included, 11 reported outcomes for two different approaches in the same study [ 10 , 33 , 40 , 43 , 49 , 50 , 52 , 69 , 79 , 84 ], and one study reported three approaches [ 74 ], resulting in 75 total study arms. Eight studies reported the DAA, five reported the ALA, six reported the DLA, and 56 studies reported the PLA (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 63 articles included, 11 reported outcomes for two different approaches in the same study [ 10 , 33 , 40 , 43 , 49 , 50 , 52 , 69 , 79 , 84 ], and one study reported three approaches [ 74 ], resulting in 75 total study arms. Eight studies reported the DAA, five reported the ALA, six reported the DLA, and 56 studies reported the PLA (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…15 MDM implants have been shown to decrease instability in patients at high risk of dislocation. Dhawan et al 16 reported zero dislocations among a cohort of 227 patients undergoing pTHA who were identified as high risk for instability. In terms of rTHA, the literature is similarly positive, with a 2022 retrospective review by Park et al 17 demonstrating no re-dislocations in 34 patients undergoing rTHA for recurrent dislocation.…”
Section: Discussionmentioning
confidence: 99%
“…Utilisation of dual mobility cups could also represent a practical solution in patients with a stiff spine and a bail-out option in cases where persistent impingement is evident [ 33 , 34 ]. It has been shown that they can minimise dislocations after primary THA [ 35 ] and a recent study from the Australian Orthopaedic Association National Joint Replacement Registry (AOANJRR) has reported 99.1% survival at 14 months [ 36 ]. While dual mobility articulations could help mitigate the dislocation risk, one should consider that a real benefit regarding ROM is seen with the larger acetabular cups.…”
Section: Discussionmentioning
confidence: 99%